Evaluation Of Potential Antimicrobial Activity Of Some Medicinal Plants Against Common Food-Borne Pathogenic Organism - S. BAKKIYARAJ; S.PANDIYARAJ (International Journal of Pharma and Bio Sciences, 2011)
Indian Medicinal plants contain many antimicrobial agents and properties. Hence, an attempt has been made to find out newer components from the Indian Medicinal plants Natural antimicrobials can be derived from plants, animal tissues, or microorganisms. The shortcomings of the drugs available today, propel the discovery of new pharmacy-therapeutic agents in medicinal plants. To determine the potential and promote the use of herbal medicine, in the present study of aqueous and ethanoloic extract of 5 medicinal plant tested leaves of Azadirachta indica (Meliaceae), Portulaca oleracea (Portulacaceae) , Euphorbia hirta (Euphorbiaceae) , Gmelina asiatica (Verbenaceae), Santalum album((Santalaceae), were screened for their anti-microbial activity against seven species of micro organism Escherichia coli, ,Bacillus subtilis, , Pseudomonas aeruginosa , Salmonella typhimurium ,Staphylococcus aureus, Candida albicans and Aspergillus Niger. The susceptibility of the microorganisms to the extracts of these plants was compared with each other and with selected antibiotics. The antimicrobial activities of these plants were discussed according to their phytochemical components.